Mitochondria and pluripotency: from established models to emerging roles in adult stem cells - Labusca, Luminita; Zara-Danceanu, Camelia-Mihaela (Frontiers in Bioengineering and Biotechnology, 2025)
Pluripotency, once considered an exclusive attribute of early embryonic cells, is increasingly recognized in certain adult tissue-derived stem cell populations, challenging traditional developmental paradigms. Recent findings highlight mitochondria as key regulators of cellular identity, integrating metabolic status, redox signaling, and epigenetic cues to influence stemness and differentiation. This review synthesizes current knowledge on mitochondrial features (from morphology, dynamics, to bioenergetics and correlation to cellular epigenetic status) in pluripotent stem cells (ESCs and iPSCs) as well as in multipotent adult tissue stem cells (ASC) emphasizing transitions between glycolytic and oxidative metabolism during reprogramming and lineage specification. Particular attention is given to existing evidence on adult pluripotent-like stem cells, including VSELs, MAPCs, MUSE cells, MIAMI, and DFATs, which remain incompletely characterized but demonstrate promising regenerative capacities. While direct data on mitochondrial behavior in these cells are sparse, parallels with multipotent adult stem cells as well as with ESC and IPSCs suggest a model wherein stress-induced bioenergetic shifts, ROS signaling, and mitochondrial remodeling act as modulators of latent pluripotency. Understanding these mechanisms could offer insights on adult pluripotent stem cell role in orchestrating regeneration during major trauma or environmental stress as well as on their distinctive responsiveness compared to ASC. Such an approach could inform future strategies in regenerative medicine, offering novel insights into how adult cells might resume developmental plasticity through mitochondrial balance, intercellular transfer and networking.